Incremental polynomial time dualization of quadratic functions and a subclass of degree-k functions - Karasan, O. Ekin (Annals of operations research, 2011)
We consider the problem of dualizing a Boolean function f represented by a DNF. In its most general form, this problem is commonly believed not to be solvable by a quasi-polynomial total time algorithm. We show that if the input DNF is quadratic or is a special degree- k DNF, then dualization turns out to be equivalent to hypergraph dualization in hypergraphs of bounded degree and hence it can be achieved in incremental polynomial time.